2013
DOI: 10.1111/tri.12131
|View full text |Cite|
|
Sign up to set email alerts
|

Alterations of naïve and memory B-cell subsets are associated with risk of rejection and infection in heart recipients

Abstract: Rejection and infection are relevant causes of mortality in heart recipients. We evaluated the kinetics of the maturation status of B lymphocytes and its relationship with acute cellular rejection and severe infection in heart recipients. We analyzed B-cell subsets using 4-color flow cytometry in a prospective follow-up study of 46 heart recipients. Lymphocyte subsets were evaluated at specific times before and up to 1 year after transplantation. Higher percentages of pretransplant classswitched memory B cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…It is tempting to speculate that a protective effect of rituximab in immunologically high-risk patients could be explained by reducing the relatively high pretransplant levels of memory B cells in our immunologically high-risk patients. Indeed, an increase in circulating memory B cells has been associated with acute rejection in pediatric renal transplant recipients (17), while heart transplant recipients with higher percentages of na€ ıve B cells had a lower risk of acute rejection (18). However, we and others have previously shown that memory B cells are more resistant to depletion by rituximab than na€ ıve B cells (19,20).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…It is tempting to speculate that a protective effect of rituximab in immunologically high-risk patients could be explained by reducing the relatively high pretransplant levels of memory B cells in our immunologically high-risk patients. Indeed, an increase in circulating memory B cells has been associated with acute rejection in pediatric renal transplant recipients (17), while heart transplant recipients with higher percentages of na€ ıve B cells had a lower risk of acute rejection (18). However, we and others have previously shown that memory B cells are more resistant to depletion by rituximab than na€ ıve B cells (19,20).…”
Section: Discussionmentioning
confidence: 88%
“…Indeed, an increase in circulating memory B cells has been associated with acute rejection in pediatric renal transplant recipients (17), while heart transplant recipients with higher percentages of na€ ıve B cells had a lower risk of acute rejection (18). However, we and others have previously shown that memory B cells are more resistant to depletion by rituximab than na€ ıve B cells (19,20).…”
Section: Rituximab In Renal Transplantationmentioning
confidence: 89%
“…In animal models, the reduction in naïve B cells promotes Cryptococcus dissemination (35) and the lower biodiversity of BCR sequences with SHM in patients with SLE (34) may diminish the B cell repertoire to combat infections. Also, the lower pool of naïve B cells could lead to less class-switched memory B cells, which are known to be fundamental in the prevention of infections in other clinical conditions (36). The combination of a lower naïve B cell repertoire and diminished SHM may explain the increased risk of infection in SLE patients, although further studies are required to assess if different B cell subsets are involved in infection development in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, increased expression of CD31 on plasma cells correlates with the mRNA expression profile in plasmablasts and plasma cells [ 35 ]. The investigation of CD31 and CD39 expression can be a useful tool for plasma cell characterization and may allow uncovering subsets with specific roles during an immune response as recently reported [ 60 , 61 ]. Furthermore, the coexpression of CD31 and its ligand CD38, on plasma cells [ 62 ] suggests a role for this interaction in the plasma cell survival niche as already proposed for leukemia cells [ 52 , 55 ].…”
Section: Discussionmentioning
confidence: 99%